Healthy foods from tubers - Padmaja, G.; Sheriff, J. T.; Sajeev, M. S. (Indian Horticulture, 2019)
The tropical tubers are well-known as energy storehouses of nature, but their food value is gradually diminishing. With rapidly changing lifestyle of people and increasing migration to urban areas, there is an increase in demand for processed foods. The occurrence of diseases such as diabetes, cardiovascular problems, obesity and other complications have led to an imminent need for development of value-added foods having additional food value. Such foods are pasta which also combine low glycaemic property, extruded snacks with low oil content, fried snacks with high nutritional value, value-added products of sweet potato etc. Minimally processed products have been developed from cassava and elephant-foot yam as a boon to exporters.